Incidence of post partum anoestrus in buffaloes - KUNJ, VIVEK; SINGH, A P; SINGH, C; AKHTAR, M H (The Indian Journal of Animal Reproduction, 2023)
Study on prevalence of anoestrus in buffalo cows was carried out monthwise and seasonwise basis. Outof 237 casesof reproductive disorders, 81 (34.18%) were anestrus. The prevalence of anestrus in buffalo cowsduring different months and seasons ranged from 14.28 to 51. 72% and 28.30 to 38. 75%, respectively. The highestpercentage (51.72%) was recorded during August while the lowest (14.28%) during June. The effect of month andseason on prevalence of anestrus was not significant.
Keywords: Incidence; post partum anestrus; buffalo